Conflict Resolution Through Agrarian Conflict Management In Mekarjaya Village - Willya Achmad (Peneliti.net, 2023)
It is impossible to live in a society without encountering the phenomenon of conflict. The agrarian dispute that took place in Mekarjaya Village, which is located in Kertajati District, Majalengka Regency, was one of the conflicts that took place in the village. This conflict arose as a result of the local community and Perum Perhutani having opposing goals and objectives in relation to the use of the land. Several parties on both sides of this agrarian conflict are attempting to resolve their differences through mediation in order to bring an end to the fighting. In this investigation, qualitative research approaches are utilized, and literature reviews serve as a means for data collecting. Gathered data then undergoes processing, which is broken down into three distinct phases: data reduction, data analysis, and conclusion drawing. Mekarjaya Village in Kertajati District, Majalengka Regency, is putting forth an effort to end agrarian disputes as a direct result of this study. To be more specific, these initiatives involve reaching a new agreement among locals by enabling farmers to engage in agricultural operations on forestry land, however only with certain kinds of plants like rubber plants and eucalyptus plants. In order to preserve the local ecosystem, these plants are strictly regulated.